PENERAPAN METODE ACTIVITY BASED COSTING (ABC) PADA PERUSAHAAN XYZ - Yusnia Sinambela; Yetty Elizabet (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2018)
PT. XYZ is a national private company engaged in thermorforming plastic packaging industry and injection molding. Plastic thermoforming produced are types of printing (plastic cup) and plastic cup (clear plastic cup) while for plastic injection molding product is loly (plastic tube). So far in calculating the cost of production of PT. XYZ uses traditional cost calculations where the distribution of overhead (Fixed Cost) is evenly distributed for all product types although the process is different because the traditional cost calculation does not calculate the cost of production in detail. Based on the background, the authors use Activity Based Costing method in the company's financial calculations. From the calculation, the average cost of production obtained by using activity based costing method for clear cup is Rp.21 / gr, for cup printing Rp.12,07 / gr while the average cost of production of cup lolly is Rp. 34.23 / gr. The average cost of production obtained by using traditional method for clear cups is Rp.19,55 / gr, for cup printing Rp.19,55 / gr while the average production cost of cup lolly is Rp. 19.55 / gr. The cost of clear cups production using ABC method and traditional method with difference is Rp.1,45 / gr, the difference for cup printing is Rp.7,48 / gr while for cup lolly the cost difference is Rp.14,68 / gr. Products that undercost is cup printing, while the overcost is a clear cup and cup lolly